New records of the water mite genera Atractides Koch and Sperchon Kramer from the Balkan, with the description of one new species - Pesic, Vladimir M. (Zootaxa, 2003)
Four water mite species of the genera Atractides and Sperchon (Acari: Hydrachnidia) are reported from Serbia and Crna Gora, Bosnia and Herzegovina, Macedonia and Bulgaria. Sperchon vesnae is described as a new species; first description are given of the female of Atractides longisetus Pesic, 2002; first records from the Balkan peninsula are given of Sperchon longissimus Viets, 1920, and Atractides cf. lunipes Lundblad, 1956. The latter is a rare water mite species previously known only from the French Pyrenees.